2019
DOI: 10.1200/jco.2019.37.15_suppl.e14125
|View full text |Cite
|
Sign up to set email alerts
|

Real-life use of nivolumab and pembrolizumab in four adult university teaching hospitals in Québec, Canada.

Abstract: e14125 Background: Nivolumab and pembrolizumab, two anti-PD1 agents, were approved and funded in Québec since 2016 for non small cell lung cancer (NSCLC), renal cell carcinoma (RCC) and melanoma. The objectives were to describe and assess the “real-life” use, efficacy and security of nivolumab and pembrolizumab in NSCLC, RCC and melanoma in the general population. Methods: Medical records of every patient who received nivolumab or pembrolizumab between January 1st 2011 and October 31st 2017 were reviewed retr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…Ksienski et al, in their study conducted in six cancer centers including 49 previously treated aNSCLC patients, reported a median OS of 13.4 months (95% CI, 8.1‐NA), similar to our results 10 . Another multicentric retrospective cohort study, including 61 patients receiving pembrolizumab as second‐line therapy, reported a median OS of 12.67 months and a median PFS of 6.03 months 11 , also markedly consistent with our findings.…”
Section: Discussionsupporting
confidence: 92%
“…Ksienski et al, in their study conducted in six cancer centers including 49 previously treated aNSCLC patients, reported a median OS of 13.4 months (95% CI, 8.1‐NA), similar to our results 10 . Another multicentric retrospective cohort study, including 61 patients receiving pembrolizumab as second‐line therapy, reported a median OS of 12.67 months and a median PFS of 6.03 months 11 , also markedly consistent with our findings.…”
Section: Discussionsupporting
confidence: 92%